The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.marpolbul.2014.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of microcystins (cyanobacteria hepatotoxins) from the reservoir of Isahaya Bay, Japan, into the marine and surrounding ecosystems as a result of large-scale drainage

Abstract: In the artificial reservoir of the Isahaya reclaimed land, Nagasaki, Japan, algal blooms have become an annual event, dominated primarily by the microcystin (MC) producing cyanobacteria Microcystis aeruginosa. Although the majority of MCs are either degraded by bacteria or washed out to sea, some remain in the sediment of the reservoir and bay throughout the year. As a result, they also accumulate in aquatic organisms (mullet, oyster, etc.) that inhabit the reservoir and surrounding areas, as well as midge fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Our lack of awareness of the potential importance of these aspects for ecosystem health has been underscored by recent mortality events among sea otters in the aforementioned Monterey Bay National Marine Sanctuary, whose cause was eventually attributed to the transfer of freshwater-derived microcystins into marine food webs at the river-sea interface in central California [30,34,35]. Subsequent studies in the northwest United States and Japan have identified contamination of marine resources from inland/freshwater sources of microcystins [31,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Our lack of awareness of the potential importance of these aspects for ecosystem health has been underscored by recent mortality events among sea otters in the aforementioned Monterey Bay National Marine Sanctuary, whose cause was eventually attributed to the transfer of freshwater-derived microcystins into marine food webs at the river-sea interface in central California [30,34,35]. Subsequent studies in the northwest United States and Japan have identified contamination of marine resources from inland/freshwater sources of microcystins [31,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Stratigraphic data from our silty site showed that sediments enriched with microcystin have been partially buried since the 2006 bloom event, with peak microcystin concentrations observed 1-2 cm below the sedimentwater interface. Other studies have also documented the presence of microcystin in sediments (Misson et al 2012, Takahashi et al 2014, though questions about persistence and bioavailability remain. Based on the relative contributions of silty (44%) and sandy (55%) areas in the Lithuanian portion of the Curonian Lagoon (Zilius et al 2014) we estimate a total mass of P a g e | 14 84 kg of microcystin in the 0-10 cm sediment layer.…”
Section: P a G E | 13mentioning
confidence: 99%
“…Finally, filter-feeding estuarine and marine invertebrates are a potential source of human and animal exposure to freshwater cyanotoxins originating in coastal rivers [ 21 , 22 , 23 , 24 , 25 ]. For example, filter-feeding invertebrates from regions of microcystin-contaminated coastal freshwater outflow are the most likely source of microcystin intoxication for threatened southern sea otters ( Enhydra lutris nereis ) in Monterey Bay, California [ 21 ].…”
Section: Example Animal Sentinel Systems and Eventsmentioning
confidence: 99%